2000
DOI: 10.1034/j.1399-6576.2000.440322.x
|View full text |Cite
|
Sign up to set email alerts
|

Less adrenergic activation during cataract surgery with total intravenous than with local anesthesia

Abstract: The presented study and available data clearly suggest that local anesthesia produces the best adrenergic and hemodynamic stability during cataract surgery. Contrary to previously reported results on inhalational anesthesia (thiopentone/enflurane), the TIVA regimen used effectively prevents the adrenergic and metabolic response during cataract surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Thus, surgery decreases the Th1/Th2 ratio, which is responsible for the suppressed cell‐mediated immunity after surgery [13]. Since anaesthesia can suppress the stress response to surgical stimulation [14–17], it may inhibit the decrease in the Th1/Th2 ratio caused by surgery.…”
mentioning
confidence: 99%
“…Thus, surgery decreases the Th1/Th2 ratio, which is responsible for the suppressed cell‐mediated immunity after surgery [13]. Since anaesthesia can suppress the stress response to surgical stimulation [14–17], it may inhibit the decrease in the Th1/Th2 ratio caused by surgery.…”
mentioning
confidence: 99%
“…The smaller the trauma the smaller the stress response [30,31]. Minimal stress reaction, as a response to surgical stimuli from the operative field, accompanies ophthalmic procedures [32,33]. Therefore, Kushikata et al [34,35] conducted two studies in which they compared the neuroendocrine stress response to entirely intravenous anaesthesia, using propofol, with anaesthesia with balanced sevoflurane, in patients undergoing scheduled eye-related surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…TIVA (n=10) P 40% MAP time (s) 378 (104) 498 (95) 0.02* 40% epinephrine (pg ml ±1 ) Q 10 4 1.6 (0.8) 5.6 (3.1) <0.01* 40% norepinephrine (pg ml ±1 ) Q 10 4 8. advantageous with regard to maintaining haemodynamics against the development of asphyxia-induced stress. Several investigators have reported that TIVA with propofol and opioids effectively blunts the adrenergic response to surgical stress, with a consecutive reduction in plasma catecholamine concentrations.…”
Section: Iso¯urane (N=10)mentioning
confidence: 99%